LEGAL COLONIALITY AND GENDER VIOLENCE IN BRAZILIAN POLITICS - Magalhaes, Júlia Cristina; Pereira, Flavia Souza Máximo (Suffragium - Scientific Journal of the Regional Electoral Court of Ceará (TRE-CE), 2025)
The current structure of Brazilian society reflects a colonial power pattern that established a racist heterocispatriarchy, in which white male domination over women, in all their plurality, prevails. This power pattern, known as the coloniality of gender, perpetuates women’s subordination through an intersectional perspective, including in the political sphere. In this space, the coloniality of gender manifests in various forms of political violence against women, such as harassment, coercion, humiliation, persecution, and threats, aiming to disqualify and discourage them from engaging in disruptive political actions. This situation restricts women’s full and equal participation in power structures, undermining one of the fundamental principles of the democratic regime: representativeness. Furthermore, by creating a hostile environment, it discourages female participation in politics and perpetuates an exclusionary and unequal structure, compromising the legitimacy of the democratic system. Through a legal-theoretical methodology based on the analysis of qualitative and quantitative data, a review of scientific literature, and legislation, this study seeks to demonstrate that while laws combating political gender violence represent important legal milestones in addressing this issue, they still uphold the sexual-racial division of labor established during colonization. Therefore, it is necessary to understand the legal gaps produced by coloniality to ensure the effectiveness of measures against political gender violence in Brazil and to guarantee the full exercise of democracy in political spaces.